Association of asthma and bronchiectasis: Mendelian randomization analyses and observational study - Rui Fan; Hao Qian; Jia-Yan Xu; Jia-Yi Wang; Yue Su; Jia-Wei Yang; Fang Jiang; Wei-Jun Cao; Jin-Fu Xu (Respiratory Research)
Abstract Background Previous studies have demonstrated that asthma is closely associated with bronchiectasis, however, the causal relationship between asthma and bronchiectasis has not been investigated in depth. Therefore, this study aims to explore the causal relationship and to identify potential factors that mediate between these two diseases. Method All the necessary summarized information were obtained from publicly available genome-wide association study (GWAS). Two-sample Mendelian randomization (two-sample MR) was employed to explore the causal relationship between asthma and bronchiectasis, with an additional dataset used for validation. Heterogeneity and pleiotropy analyses were utilized to verify the robustness of the results. Subsequently, mediation MR analyses were performed to identify potential mediating factors. Lastly, a retrospective observational study was conducted to validate the findings. Result Preliminary inverse-variance weighted (IVW) results indicated there was a causal effect of asthma on bronchiectasis (odds ratio [OR] = 1.228, 95% confidence interval [CI]: 1.077–1.400, P = 0.002). Repetition validation yielded a consistent result. Mediation MR analysis demonstrated that the presence of nasal polyps (OR = 1.063, 95% CI: 1.015–1.113, mediation ratio = 30.492%, P = 0.009), acute sinusitis (OR = 1.062, 95% CI: 1.009–1.118, mediation ratio = 30.157%, P = 0.018), chronic sinusitis (OR = 1.085, 95% CI: 1.024–1.150, mediation ratio = 40.677%, P = 0.005), and peripheral eosinophil counts (OR = 1.013, 95% CI: 1.000–1.026, mediation ratio = 6.514%, P = 0.042) served as significant mediators in the occurrence and development of bronchiectasis induced by asthma. Furthermore, a retrospective observational study observed that bronchiectasis patients with asthma had a higher prevalence of sinusitis (5.043% vs 2.971%, P < 0.001), nasal polyps (0.536% vs 0.152%, P < 0.001), and rhinitis (13.197% vs 1.860%, P < 0.001). The ratio (1.950 (0.500, 5.600) vs 1.500 (0.500, 2.600), P = 0.006) and counts (0.125 (0.040, 0.363) vs 0.090 (0.030, 0.160), P < 0.001) of peripheral blood eosinophils were also elevated in bronchiectasis patients with asthma. Conclusion The MR analysis uncovered a notable genetic association between asthma and bronchiectasis, which was partially mediated by sinusitis, nasal polyps, and eosinophils. A subsequent retrospective study provided further evidence by demonstrating that bronchiectasis patients with asthma had a higher prevalence of sinusitis, nasal polyps, an elevated proportion of eosinophils, and higher eosinophil counts.